Gallium oxide fiber and preparation method thereof
Through oxygen pretreatment of gallium-based liquid metal and atmosphere, temperature and time adjustment in the tube furnace, the problems of complex preparation process, high cost and low yield of gallium oxide fibers are successfully solved, and efficient and simple preparation methods and crystal phase control are achieved, which are suitable for industrial production.
Patent Information
- Application Number
- CN202411732096.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2025-03-14
AI Technical Summary
The existing gallium oxide fiber preparation methods have problems such as complex preparation process, high cost, low yield and difficulty in controlling the crystal phase.
Gallium-based liquid metal is used as the precursor, and the initial oxide layer is formed by oxygen pretreatment, and then the atmosphere, temperature and time are adjusted in a tube furnace to achieve selective preparation of gallium oxide fibers.
It realizes simple and efficient preparation of gallium oxide fibers, can control the growth of different crystal phases, reduce costs, and is suitable for large-scale production.
Smart Images

Figure CN119615047A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of semiconductor materials technology, and in particular to gallium oxide fibers and their preparation methods. Background Technology
[0002] Traditional gallium oxide fibers can be prepared using methods such as sol-gel, electrospinning, and chemical vapor deposition (CVD). Among these methods, the sol-gel precipitation process is difficult to control, and agglomeration and uneven particle distribution are prone to occur. The electrospinning process suffers from electrostatic interference, affecting product quality stability, and has a relatively low yield, making it difficult to scale up industrial production. CVD requires high vacuum or a specific atmosphere, resulting in high costs and complex equipment, which is not conducive to large-scale production.
[0003] In addition, gallium oxide has different crystal phase structures such as α, β, and γ, and different crystal phases have different physicochemical properties. However, the current methods for controlling the crystal phase of gallium oxide are relatively complex. Summary of the Invention
[0004] Therefore, it is necessary to provide gallium oxide and its preparation method to address the above problems. The preparation method is simple, efficient, and can control the crystal phase of gallium oxide fibers.
[0005] A method for preparing gallium oxide fibers includes the following steps:
[0006] Gallium-based liquid metal is coated onto a substrate;
[0007] The gallium-based liquid metal is heated by introducing oxygen at a temperature less than or equal to 200°C.
[0008] A gas is introduced to carry out a heating reaction to obtain gallium oxide fibers. The gas is selected from at least one of hydrogen, air, oxygen, and inert gas. The reaction temperature is 300℃-1100℃, the heating rate is 1℃ / min-5℃ / min, and the reaction time is 0.5h-6h.
[0009] In one embodiment, the preparation method is carried out using a tube furnace.
[0010] In one embodiment, the coating mass of the gallium-based liquid metal is 0.3 mg / cm³. 2 -2mg / cm 2 .
[0011] In one embodiment, the gallium-based liquid metal is selected from at least one of liquid gallium, liquid gallium indium, liquid gallium indium tin, liquid gallium indium tin bismuth, or liquid gallium iron nickel.
[0012] In one embodiment, in the step of heating the gallium-based liquid metal by introducing oxygen, the oxygen flow rate is 50 sccm-300 sccm, the heating temperature is 50℃-200℃, the heating rate is 2℃ / min-5℃ / min, and the treatment time is 0.3h-3h.
[0013] In one embodiment, in the step of introducing gas for heating reaction, the gas flow rate is 100 sccm-500 sccm, the gas is selected from inert gases, the reaction temperature is 300℃-500℃, the heating rate is 4℃ / min-5℃ / min, and the reaction time is 0.5h-2h.
[0014] In one embodiment, in the step of introducing gas for heating reaction, the flow rate of the gas is 100 sccm-500 sccm, the gas is selected from hydrogen, the reaction temperature is 500℃-900℃, the heating rate is 3℃ / min-5℃ / min, and the reaction time is 0.5h-1.5h.
[0015] In one embodiment, in the step of introducing gas to carry out the heating reaction, the flow rate of the gas is 100 sccm-500 sccm, the gas is selected from at least one of air or oxygen, the reaction temperature is 900℃-1100℃, the heating rate is 1℃ / min-2℃ / min, and the reaction time is 3h-6h.
[0016] In one embodiment, the substrate is first ground and polished before the step of coating the gallium-based liquid metal onto the substrate.
[0017] Gallium oxide fibers obtained by the aforementioned method for preparing gallium oxide fibers.
[0018] In the preparation method of the present invention, gallium-based liquid metal is used as a precursor. After the gallium-based liquid metal is subjected to oxygen pretreatment, gallium oxide fibers of different crystal phases can be selectively obtained by adjusting and controlling the atmosphere, temperature and time of the heating reaction. The process is simple, efficient and low in cost, and suitable for large-scale production. Attached Figure Description
[0019] To more clearly illustrate the technical solutions in the embodiments of this application or the conventional technology, the drawings used in the description of the embodiments or the conventional technology will be briefly introduced below. Obviously, the drawings described below are only some embodiments of this application. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0020] Figure 1 and Figure 2 All images are SEM images of the gallium oxide fibers prepared in Example 6;
[0021] Figure 3 The image shows the energy dispersive spectroscopy (EDS) analysis of the gallium oxide fiber prepared in Example 6. Detailed Implementation
[0022] To facilitate understanding of the present invention, it will be described in more detail below. However, it should be understood that the present invention can be implemented in many different forms and is not limited to the embodiments or examples described herein. Rather, these embodiments or examples are provided to make the disclosure of the present invention more thorough and complete.
[0023] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. The terminology used herein in the specification of this invention is for the purpose of describing particular embodiments or examples only and is not intended to limit the invention. The optional scope of the term "and / or" as used herein includes any one of two or more of the related listed items, as well as any and all combinations of the related listed items, including any two related listed items, any more related listed items, or a combination of all related listed items.
[0024] In this invention, numerical ranges are involved. Unless otherwise specified, the numerical ranges are considered continuous and include the minimum and maximum values of the range, as well as every value between the minimum and maximum values. Furthermore, when the range refers to integers, it includes every integer between the minimum and maximum values of the range. Additionally, when multiple ranges are provided to describe features or characteristics, the ranges may be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges to which they are included.
[0025] The method for preparing gallium oxide fibers provided by the present invention includes the following steps:
[0026] S1, Gallium-based liquid metal is coated onto the substrate;
[0027] S2, oxygen is introduced to heat the gallium-based liquid metal at a temperature less than or equal to 200°C;
[0028] S3, a gas is introduced to carry out a heating reaction to obtain gallium oxide fiber, wherein the gas is selected from at least one of hydrogen, air, oxygen, and inert gas, the reaction temperature is 300℃-1100℃, the heating rate is 1℃ / min-5℃ / min, and the reaction time is 0.5h-6h.
[0029] Gallium-based liquid metals possess fluidity. This invention uses gallium-based liquid metals as a precursor, avoiding the agglomeration phenomenon that occurs during calcination when using solid powder precursors. Then, oxygen is used to pretreat the gallium-based liquid metal, forming an initial oxide layer on its surface, typically a thin layer of gallium oxide. This layer serves as a nucleus, promoting subsequent gallium oxide nucleation and growth, reducing nucleation energy, and resulting in more uniform gallium oxide fibers. It also prevents uneven oxygen permeation rates during heating and further oxidation, ensuring uniform oxidation of the gallium-based liquid metal in subsequent reactions and avoiding inconsistent oxidation inside and outside. Most importantly, the growth of gallium oxide with different crystal phases requires specific nucleation conditions and oxidation rates; oxygen pretreatment provides the conditions for controlling the crystal phase. Furthermore, by adjusting and controlling the atmosphere, temperature, and time of the heating reaction, gallium oxide fibers with different crystal phases can be selectively obtained. The process is simple, efficient, and low-cost, suitable for large-scale production.
[0030] Tube furnaces can flexibly control the oxidation or reduction of materials by introducing different gases as needed. At the same time, tube furnaces have a simple structure and operation, making them suitable for industrial-scale applications. Therefore, the preparation method described in this invention preferably uses a tube furnace. After coating gallium-based liquid metal onto a substrate, the substrate is placed in a tube furnace, and then oxygen is introduced to heat the gallium-based liquid metal, forming an initial oxide layer on the surface of the gallium-based liquid metal. Finally, by adjusting the atmosphere, temperature, and time in the tube furnace, gallium oxide fibers with different crystal phases can be selectively obtained. The process is simple, efficient, and low-cost.
[0031] Specifically, in step S1, the substrate is selected from graphite plate, molybdenum plate, alumina plate or silicon plate, etc.
[0032] Impurities on the substrate can cause localized non-uniform stress fields, affecting the crystal growth path and morphology of gallium oxide fibers, leading to a shift in the crystal growth direction and resulting in non-uniform or distorted gallium oxide fibers. Simultaneously, impurities on the substrate may trigger unnecessary chemical reactions during growth, generating byproducts. Especially at high temperatures, impurities on the substrate may react with gallium oxide or the growth atmosphere to form new impurities or secondary phases. These byproducts can affect the purity and structure of the fibers, and even hinder gallium oxide crystal growth. Therefore, in step S1, before coating the substrate with gallium-based liquid metal, the substrate is first ground and polished to remove impurities, making the substrate surface cleaner. This not only facilitates uniform crystal nucleation and fiber growth along a specific direction, resulting in a more consistent morphology and structure of the gallium oxide fibers, but also effectively avoids side reactions and improves the controllability of the growth process.
[0033] Optionally, in the step of grinding and polishing the substrate, it is preferable to first grind the substrate with low-grit sandpaper and then polish it with high-grit sandpaper until the surface is smooth.
[0034] In the step of coating gallium-based liquid metal onto a substrate, the coating mass of the gallium-based liquid metal is preferably 0.3 mg / cm³. 2 -2mg / cm 2 For example, 0.3 mg / cm 2 0.4 mg / cm 2 0.5 mg / cm 2 0.6 mg / cm 2 0.7 mg / cm 2 0.8 mg / cm 2 0.9 mg / cm 2 1.0 mg / cm 2 1.1 mg / cm 2 1.2 mg / cm 2 1.3 mg / cm 2 1.4 mg / cm 2 1.5 mg / cm 2 1.6 mg / cm 2 1.7 mg / cm 2 1.8 mg / cm 2 1.9 mg / cm 2 2.0 mg / cm 2 etc., or a range of any two of these values, such as 0.3 mg / cm³. 2 -1.3mg / cm 2 0.4 mg / cm 2 -1.5mg / cm 2 0.5 mg / cm 2 -1.5mg / cm 2 Thus, the coating thickness of gallium-based liquid metal can be better controlled, which is conducive to the uniform nucleation and oxidation of gallium-based liquid metal, resulting in uniform gallium oxide fibers.
[0035] Optionally, the gallium-based liquid metal is selected from at least one of liquid gallium, liquid gallium indium, liquid gallium indium tin, liquid gallium indium tin bismuth, or liquid gallium iron nickel.
[0036] In step S2, the step of heating the gallium-based liquid metal by introducing oxygen, the oxygen flow rate is preferably 50 sccm-300 sccm, such as 50 sccm, 80 sccm, 100 sccm, 120 sccm, 150 sccm, 180 sccm, 200 sccm, 220 sccm, 250 sccm, 280 sccm, 300 sccm, or any combination of these values. The heating temperature is preferably 50℃-200℃, such as 50℃, 80℃, 100℃, 120℃, 15 ... The preferred heating rate is 2℃ / min-5℃ / min, such as 2℃ / min, 3℃ / min, 4℃ / min, 5℃ / min, or any combination of these values. The preferred processing time is 0.3h-3h, such as 0.3h, 0.5h, 1h, 1.5h, 2h, 2.5h, 3h, or any combination of these values. Thus, by selecting the conditions, gallium oxide thin layers of different thicknesses can be formed on the surface of gallium-based liquid metal.
[0037] Based on step S2, in step S3, by adjusting and controlling the atmosphere, temperature and time of the heating reaction, gallium oxide fibers with different crystal phases can be selectively obtained.
[0038] Optionally, the gas flow rate is 100 sccm-500 sccm, such as 100 sccm, 150 sccm, 200 sccm, 250 sccm, 300 sccm, 350 sccm, 400 sccm, 450 sccm, 500 sccm, or any combination of these values. The gas is selected from inert gases such as nitrogen and argon. The reaction temperature is 300℃-500℃, such as 300℃, 350℃, 400℃, 450℃, 500℃, or any combination of these values. The heating rate is 4℃ / min-5℃ / min, such as 4℃ / min, 4.5℃ / min, 5℃ / min, or any combination of these values. The reaction time is 0.5h-2h, such as 0.5h, 1h, 1.5h, 2h, or any combination of these values, which can yield γ-phase gallium oxide fibers.
[0039] Optionally, the gas flow rate is 100 sccm-500 sccm, such as 100 sccm, 150 sccm, 200 sccm, 250 sccm, 300 sccm, 350 sccm, 400 sccm, 450 sccm, 500 sccm, etc., or any range of two of these values. The gas is selected from hydrogen, and the reaction temperature is 500℃-900℃, such as 500℃, 550℃, 600℃, 650℃, 700℃, etc. Gallium oxide fibers of the α phase can be obtained at temperatures of 50℃, 800℃, 850℃, 900℃, or any combination of these values, with a heating rate of 3℃ / min-5℃ / min, such as 3℃ / min, 3.5℃ / min, 4℃ / min, 4.5℃ / min, 5℃ / min, or any combination of these values, and a reaction time of 0.5h-1.5h, such as 0.5h, 1h, 1.5h, or any combination of these values.
[0040] Optionally, the gas flow rate is 100 sccm-500 sccm, for example, 100 sccm, 150 sccm, 200 sccm, 250 sccm, 300 sccm, 350 sccm, 400 sccm, 450 sccm, 500 sccm, etc., or any combination of these values. The gas is selected from at least one of air or oxygen. The reaction temperature is 900℃-1100℃, for example, 900℃, 950℃, 1000℃, 1050℃, 1100℃, etc., or any combination of these values. The heating rate is 1℃ / min-2℃ / min, for example, 1℃ / min, 1.5℃ / min, 2℃ / min, etc., or any combination of these values. The reaction time is 3h-6h, for example, 3h, 3.5h, 4h, 4.5h, 5h, 5.5h, 6h, etc., or any combination of these values, to obtain β-phase gallium oxide fibers.
[0041] The present invention also provides a gallium oxide fiber obtained by the above preparation method, comprising a fiber body and spherical particles located at the ends of the fiber body, wherein the fiber body is composed of gallium oxide (Ga2O3) and the spherical particles are composed of gallium (Ga).
[0042] The gallium oxide fiber of this invention has a high band gap and a high breakdown electric field strength, and has great development potential in the fields of high-power and high-temperature electronic devices. In particular, in power conversion equipment, gallium oxide fiber can withstand higher voltages and temperatures, meet the stringent requirements of power electronic systems for material durability, and help improve the efficiency and lifespan of power devices.
[0043] The gallium oxide fiber and its preparation method will be further described below through specific embodiments.
[0044] Example 1
[0045] A graphite substrate with a thickness of 1.5 mm and a diameter of 1 cm was sanded with 800 grit, 2000 grit and 3000 grit sandpaper respectively, and then polished with 5000 grit and 7000 grit sandpaper until the surface was smooth.
[0046] Liquid gallium metal was uniformly coated onto the graphite substrate, with a coating mass of 1 mg. The coated material was then placed in a ceramic boat and positioned at the center of a tube furnace.
[0047] 100 sccm of oxygen was introduced into the tube furnace, and the temperature was increased to 100°C at a rate of 3°C / min. The reaction time was 1 hour. After the reaction was completed, the furnace was cooled to room temperature.
[0048] Nitrogen gas at a flow rate of 200 sccm was introduced into a tube furnace, and the temperature was increased to 400°C at a rate of 5°C / min. The reaction time was 2 hours. After the reaction was completed, the furnace was cooled to room temperature to obtain γ-phase gallium oxide fibers.
[0049] Example 2
[0050] A molybdenum substrate with a thickness of 1.5 mm and a diameter of 2 cm was sanded with 800 grit, 2500 grit and 3000 grit sandpaper respectively, and then polished with 5000 grit and 7000 grit sandpaper until the surface was smooth.
[0051] Liquid gallium indium was uniformly coated onto the molybdenum substrate, with a coating mass of 1.5 mg. The coated substrate was then placed in a ceramic boat and positioned at the center of a tube furnace.
[0052] Oxygen at a flow rate of 150 sccm was introduced into the tube furnace, and the temperature was increased to 120°C at a rate of 3°C / min. The reaction time was 1 hour, and the furnace was cooled to room temperature after the reaction was completed.
[0053] Argon gas at a flow rate of 400 sccm was introduced into a tube furnace, and the temperature was increased to 500°C at a rate of 4°C / min. The reaction time was 1 hour. After the reaction was completed, the furnace was cooled to room temperature to obtain γ-phase gallium oxide fibers.
[0054] Example 3
[0055] Alumina substrates with a thickness of 1 mm and a diameter of 2 cm were sanded using 600 grit, 2500 grit, and 3000 grit sandpaper, respectively, and then polished using 5000 grit and 7000 grit sandpaper until the surface was smooth.
[0056] Liquid gallium indium tin was uniformly coated onto the alumina substrate, with a coating mass of 1.8 mg. The coated material was then placed in a ceramic boat and positioned at the center of a tube furnace.
[0057] Oxygen at a flow rate of 180 sccm was introduced into the tube furnace, and the temperature was increased to 120°C at a rate of 3°C / min. The reaction time was 1.5 h. After the reaction was completed, the furnace was cooled to room temperature.
[0058] Hydrogen gas at a flow rate of 300 sccm was introduced into a tube furnace, and the temperature was increased to 700°C at a rate of 3°C / min. The reaction time was 1 hour. After the reaction was completed, the furnace was cooled to room temperature to obtain gallium oxide fibers of the α phase.
[0059] Example 4
[0060] A 2mm thick, 1.5cm diameter silicon substrate was sanded with 600, 2000, and 3000 grit sandpaper, and then polished with 5000 and 7000 grit sandpaper until the surface was smooth.
[0061] Liquid gallium indium tin bismuth was uniformly coated onto the silicon substrate, with a coating mass of 1.2 mg. The coated substrate was then placed in a ceramic boat and positioned at the center of a tube furnace.
[0062] Oxygen at a flow rate of 180 sccm was introduced into the tube furnace, and the temperature was increased to 150°C at a rate of 2°C / min. The reaction time was 1.5 h. After the reaction was completed, the furnace was cooled to room temperature.
[0063] Hydrogen gas at a flow rate of 400 sccm was introduced into a tube furnace, and the temperature was increased to 850°C at a rate of 3°C / min. The reaction time was 1.5 h. After the reaction was completed, the furnace was cooled to room temperature to obtain α-phase gallium oxide fibers.
[0064] Example 5
[0065] A silicon substrate with a thickness of 1.5 mm and a diameter of 1.5 cm was sanded with 800 grit, 2000 grit, 2500 grit and 3000 grit sandpaper respectively, and then polished with 5000 grit and 7000 grit sandpaper until the surface was smooth.
[0066] Liquid gallium indium tin was uniformly coated onto the silicon substrate, with a coating mass of 1.5 mg. The coated substrate was then placed in a ceramic boat and positioned at the center of a tube furnace.
[0067] 150 sccm of oxygen was introduced into the tube furnace, and the temperature was increased to 120°C at a rate of 2°C / min. The reaction time was 2.5 h. After the reaction was completed, the furnace was cooled to room temperature.
[0068] Oxygen at a flow rate of 300 sccm was introduced into a tube furnace, and the temperature was increased to 950°C at a rate of 2°C / min. The reaction time was 6 h. After the reaction was completed, the furnace was cooled to room temperature to obtain gallium oxide fibers of the β phase.
[0069] Example 6
[0070] A graphite substrate with a thickness of 1.5 mm and a diameter of 1 cm was sanded with 800 grit, 2000 grit, 2500 grit and 3000 grit sandpaper respectively, and then polished with 5000 grit and 7000 grit sandpaper until the surface was smooth.
[0071] Liquid gallium-iron-nickel metal was uniformly coated onto the graphite substrate, with a coating mass of 1 mg. The coated material was then placed in a ceramic boat and positioned at the center of a tube furnace.
[0072] 120 sccm of oxygen was introduced into the tube furnace, and the temperature was increased to 150°C at a rate of 3°C / min. The reaction time was 2 hours. After the reaction was completed, the furnace was cooled to room temperature.
[0073] Air at a flow rate of 400 sccm was introduced into a tube furnace, and the temperature was increased to 1100℃ at a rate of 1℃ / min. The reaction time was 5 h. After the reaction was completed, the furnace was cooled to room temperature to obtain β-phase gallium oxide fibers.
[0074] from Figure 1 and Figure 2 It can be seen that the gallium oxide fiber obtained in this embodiment has a highly amorphous microstructure and spherical particles at the ends, combined with... Figure 3 It can be seen that in gallium oxide fiber, the fiber body is composed of gallium oxide, while the spherical particles at the ends of the fiber body are composed of gallium.
[0075] Comparative Example 1
[0076] A graphite substrate with a thickness of 1.5 mm and a diameter of 1 cm was sanded with 800 grit, 2000 grit and 3000 grit sandpaper respectively, and then polished with 5000 grit and 7000 grit sandpaper until the surface was smooth.
[0077] Liquid gallium metal was uniformly coated onto the graphite substrate, with a coating mass of 1 mg. The coated material was then placed in a ceramic boat and positioned at the center of a tube furnace.
[0078] Nitrogen gas at a flow rate of 200 sccm was introduced into a tube furnace, and the temperature was increased to 400°C at a rate of 5°C / min. The reaction time was 2 hours. After the reaction was completed, the furnace was cooled to room temperature, but no gallium oxide fibers were obtained.
[0079] Comparative Example 2
[0080] A graphite substrate with a thickness of 1.5 mm and a diameter of 1 cm was sanded with 800 grit, 2000 grit and 3000 grit sandpaper respectively, and then polished with 5000 grit and 7000 grit sandpaper until the surface was smooth.
[0081] Liquid gallium metal was uniformly coated onto the graphite substrate, with a coating mass of 1 mg. The coated material was then placed in a ceramic boat and positioned at the center of a tube furnace.
[0082] 100 sccm of oxygen was introduced into the tube furnace, and the reaction was carried out at room temperature for 1 hour.
[0083] Nitrogen gas at a flow rate of 200 sccm was introduced into a tube furnace, and the temperature was increased to 400°C at a rate of 5°C / min. The reaction time was 2 hours. After the reaction was completed, the furnace was cooled to room temperature, but no gallium oxide fibers were obtained.
[0084] Comparative Example 3
[0085] A graphite substrate with a thickness of 1.5 mm and a diameter of 1 cm was sanded with 800 grit, 2000 grit and 3000 grit sandpaper respectively, and then polished with 5000 grit and 7000 grit sandpaper until the surface was smooth.
[0086] Liquid gallium metal was uniformly coated onto the graphite substrate, with a coating mass of 1 mg. The coated material was then placed in a ceramic boat and positioned at the center of a tube furnace.
[0087] 100 sccm of oxygen was introduced into the tube furnace, and the temperature was increased to 100°C at a rate of 3°C / min. The reaction time was 1 hour. After the reaction was completed, the furnace was cooled to room temperature.
[0088] Carbon dioxide at 200 sccm was introduced into a tube furnace, and the temperature was increased to 400°C at a rate of 5°C / min. The reaction time was 2 hours. After the reaction was completed, the furnace was cooled to room temperature, but no gallium oxide fibers were obtained.
[0089] Comparative Example 4
[0090] A 2mm thick, 1.5cm diameter silicon substrate was sanded with 600, 2000, and 3000 grit sandpaper, and then polished with 5000 and 7000 grit sandpaper until the surface was smooth.
[0091] Liquid gallium indium tin bismuth was uniformly coated onto the silicon substrate, with a coating mass of 1.2 mg. The coated substrate was then placed in a ceramic boat and positioned at the center of a tube furnace.
[0092] Hydrogen gas at a flow rate of 400 sccm was introduced into a tube furnace, and the temperature was increased to 850°C at a rate of 3°C / min. The reaction time was 1.5 h. After the reaction was completed, the furnace was cooled to room temperature, but no gallium oxide fibers were obtained.
[0093] Comparative Example 5
[0094] A 2mm thick, 1.5cm diameter silicon substrate was sanded with 600, 2000, and 3000 grit sandpaper, and then polished with 5000 and 7000 grit sandpaper until the surface was smooth.
[0095] Liquid gallium indium tin bismuth was uniformly coated onto the silicon substrate, with a coating mass of 1.2 mg. The coated substrate was then placed in a ceramic boat and positioned at the center of a tube furnace.
[0096] Oxygen at 180 sccm was introduced into the tube furnace, and the reaction was carried out at room temperature for 1.5 hours.
[0097] Hydrogen gas at a flow rate of 400 sccm was introduced into a tube furnace, and the temperature was increased to 850°C at a rate of 3°C / min. The reaction time was 1.5 h. After the reaction was completed, the furnace was cooled to room temperature, but no gallium oxide fibers were obtained.
[0098] Comparative Example 6
[0099] A 2mm thick, 1.5cm diameter silicon substrate was sanded with 600, 2000, and 3000 grit sandpaper, and then polished with 5000 and 7000 grit sandpaper until the surface was smooth.
[0100] Liquid gallium indium tin bismuth was uniformly coated onto the silicon substrate, with a coating mass of 1.2 mg. The coated substrate was then placed in a ceramic boat and positioned at the center of a tube furnace.
[0101] Oxygen at a flow rate of 180 sccm was introduced into the tube furnace, and the temperature was increased to 150°C at a rate of 2°C / min. The reaction time was 1.5 h. After the reaction was completed, the furnace was cooled to room temperature.
[0102] Carbon dioxide at 400 sccm was introduced into a tube furnace, and the temperature was increased to 850°C at a rate of 3°C / min. The reaction time was 1.5 h. After the reaction was completed, the furnace was cooled to room temperature, but no gallium oxide fibers were obtained.
[0103] Comparative Example 7
[0104] A graphite substrate with a thickness of 1.5 mm and a diameter of 1 cm was sanded with 800 grit, 2000 grit, 2500 grit and 3000 grit sandpaper respectively, and then polished with 5000 grit and 7000 grit sandpaper until the surface was smooth.
[0105] Liquid gallium-iron-nickel metal was uniformly coated onto the graphite substrate, with a coating mass of 1 mg. The coated material was then placed in a ceramic boat and positioned at the center of a tube furnace.
[0106] Air at a flow rate of 400 sccm was introduced into the tube furnace, and the temperature was increased to 1100℃ at a rate of 1℃ / min. The reaction time was 5 hours. After the reaction was completed, the furnace was cooled to room temperature, but no gallium oxide fibers were obtained.
[0107] Comparative Example 8
[0108] A graphite substrate with a thickness of 1.5 mm and a diameter of 1 cm was sanded with 800 grit, 2000 grit, 2500 grit and 3000 grit sandpaper respectively, and then polished with 5000 grit and 7000 grit sandpaper until the surface was smooth.
[0109] Liquid gallium-iron-nickel metal was uniformly coated onto the graphite substrate, with a coating mass of 1 mg. The coated material was then placed in a ceramic boat and positioned at the center of a tube furnace.
[0110] Oxygen at 120 sccm was introduced into the tube furnace, and the reaction was carried out at room temperature for 2 hours.
[0111] Air at a flow rate of 400 sccm was introduced into the tube furnace, and the temperature was increased to 1100℃ at a rate of 1℃ / min. The reaction time was 5 hours. After the reaction was completed, the furnace was cooled to room temperature, but no gallium oxide fibers were obtained.
[0112] Comparative Example 9
[0113] A graphite substrate with a thickness of 1.5 mm and a diameter of 1 cm was sanded with 800 grit, 2000 grit, 2500 grit and 3000 grit sandpaper respectively, and then polished with 5000 grit and 7000 grit sandpaper until the surface was smooth.
[0114] Liquid gallium-iron-nickel metal was uniformly coated onto the graphite substrate, with a coating mass of 1 mg. The coated material was then placed in a ceramic boat and positioned at the center of a tube furnace.
[0115] 120 sccm of oxygen was introduced into the tube furnace, and the temperature was increased to 150°C at a rate of 3°C / min. The reaction time was 2 hours. After the reaction was completed, the furnace was cooled to room temperature.
[0116] Carbon dioxide at 400 sccm was introduced into a tube furnace, and the temperature was increased to 1100℃ at a rate of 1℃ / min. The reaction time was 5 h. After the reaction was completed, the furnace was cooled to room temperature, but no gallium oxide fibers were obtained.
[0117] The technical features of the above embodiments can be combined in any way. For the sake of brevity, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0118] The embodiments described above are merely illustrative of several implementations of the present invention, and while the descriptions are relatively specific and detailed, they should not be construed as limiting the scope of the invention patent. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention, and these all fall within the protection scope of the present invention. Therefore, the protection scope of this invention patent should be determined by the appended claims.
Claims
1. A method for preparing gallium oxide fiber, characterized in that: The following steps are involved: coating a gallium-based liquid metal on a substrate; Passing oxygen to heat the gallium-based liquid metal, wherein the heating temperature is less than or equal to 200° C.; Gas is introduced for heating reaction to obtain gallium oxide fiber, wherein the gas is selected from at least one of hydrogen, air, oxygen, and inert gas, the reaction temperature is 300°C-1100°C, the heating rate is 1°C / min-5°C / min, and the reaction time is 0.5h-6h.
2. The method for preparing gallium oxide fiber according to claim 1, characterized in that: The preparation method is carried out using a tube furnace.
3. The method for preparing gallium oxide fiber according to claim 1 or 2, characterized in that: The coating mass of the gallium-based liquid metal is 0.3 mg / cm 2 -2mg / cm 2 .
4. The method for preparing gallium oxide fiber according to claim 1 or 2, characterized in that: The gallium-based liquid metal is selected from at least one of liquid metal gallium, liquid metal gallium indium, liquid metal gallium indium tin, liquid metal gallium indium tin bismuth or liquid metal gallium iron nickel.
5. The method for preparing gallium oxide fiber according to claim 1 or 2, characterized in that: In the step of introducing oxygen to heat the gallium-based liquid metal, the oxygen flow rate is 50sccm-300sccm, the heating temperature is 50°C-200°C, the heating rate is 2°C / min-5°C / min, and the treatment time is 0.3h-3h.
6. The method for preparing gallium oxide fiber according to claim 1 or 2, characterized in that: In the step of introducing gas for heating reaction, the flow rate of the gas is 100sccm-500sccm, the gas is selected from inert gas, the reaction temperature is 300℃-500℃, the heating rate is 4℃ / min-5℃ / min, and the reaction time is 0.5h-2h.
7. The method for preparing gallium oxide fiber according to claim 1 or 2, characterized in that: In the step of introducing gas for heating reaction, the flow rate of the gas is 100sccm-500sccm, the gas is selected from hydrogen, the reaction temperature is 500℃-900℃, the heating rate is 3℃ / min-5℃ / min, and the reaction time is 0.5h-1.5h.
8. The method for preparing gallium oxide fiber according to claim 1 or 2, characterized in that: In the step of introducing gas for heating reaction, the flow rate of the gas is 100sccm-500sccm, the gas is selected from at least one of air or oxygen, the reaction temperature is 900℃-1100℃, the heating rate is 1℃ / min-2℃ / min, and the reaction time is 3h-6h.
9. The method for preparing gallium oxide fiber according to claim 1 or 2, characterized in that: Before coating the gallium-based liquid metal on the substrate, the substrate is first ground and polished.
10. A gallium oxide fiber obtained by the method for preparing gallium oxide fiber according to any one of claims 1 to 9.